PEMODELAN INVERSI DATA MAGNETOTELLURIK 1-D MENGGUNAKAN METODA GENETIC ALGORITHM (GA) DENGAN POPULASI MICRO GENETIC ALGORITHM KASUS 3 LAYER DAN 5 LAYER - Nia Maharani (Jurnal Santiaji Pendidikan (JSP), 2018)
This paper discusses non-linear inversion method with Genetic Algorithm (GA) which inspired by natural selection process (survival for the fittest) and genetic using 20 populations (micro genetic algorithm). The method is applied to 1-D magnetotelluric inverted data with model parameter is resistivity as a function of depth. This research only uses synthetic data obtained from synthetic model. The model is homogeneous earth model with 3 and 5 layers. Perturbation of model is performed until minimum misfit between theoritical and observation data achieved. The 3 layers and 5 layers inversion processes are applied to 3 layers and 5 layers earth model respectively, with satisfactory results in other words it can reproduce the synthetic model.